Analysis of drug resistance genes of integrons in clinical isolates of Escherichia coli from elderly bloodstream infections: Drug resistance genes of integrons of E. coli - Liu, Wei; Zhao, Fangjian; Chen, Jian (Cellular and Molecular Biology, 2022)
This experiment was carried out to provide a basis for the treatment of clinical bloodstream infections by analyzing the drug resistance characteristics and integrated gene distribution of Escherichia coli in bloodstream infections in elderly patients. For this aim, E. coli were collected for bacterial identification and drug sensitivity testing from bloodstream infections in elderly patients in the hospital from January 2016 to December 2019. ESBLs positive strains were assayed for genotypes and their integron carriage rates by PCR amplification. The characteristics and differences of various genotype rates were compared and analyzed. Results showed that a total of 230 E. coli strains were isolated. The detection rate of ESBLs-producing bacteria was 37.39 %. ESBLs-producing E. coli showed a high rate of resistance to cefepime, levofloxacin, cotrimoxazole, and ticarcillin/clavulanic acid (>40%). The resistance rate of 230 strains of E. coli to meropenem, minocycline, amikacin, gentamicin and cefoxitin was less than 20%. Among the ESBLs-producing E. coli in bloodstream infections in elderly patients, CTX-M-9 accounted for 27.91%, CTX-M-2 for 17.44%, and SHV for 13.95%. The detection rate of type I integrated genes was 41.30%, and type II and III integrated genes were not detected. ESBLs-producing genotyping-positive bacteria were detected with more than 50% of type I integrated genes. It was concluded that type I integrated genes in ESBLs-producing E. coli isolated from elderly patients carried resistance genes such as CTX-M-9 and CTX-M-2 aggravating multi-drug resistance in bacteria.